(untitled) (Education in the 21st Century, 2023)
The purpose of the study is to clearly define the technology of learning in cooperation, methods for developing cooperation skills, the rules for implementing learning in cooperation, the stages of its implementation and the features of using the Armenian language in the university course. Our task is to reveal the essence of the technology of learning in cooperation, the advantages and restrictions of the methods implemented on the basis of the principles of cooperation, the pedagogical problems that arise when using these methods and ways of their solution. The general scientific logical method, as well as a private or special method of analysis and comparison were used in a comprehensive study of the problem put forward within the framework of the topic. The formation of cooperation skills as an alternative pedagogical approach also leads to a change in the functions of a teacher. The main task of the educator becomes the creation of appropriate conditions for the development of student’s cooperation skills: the creation of a learning environment that implies a democratic, respectful style of communication, the active participation of all the students, taking into account the characteristics and level of knowledge of each student. The use of technology of learning in collaboration creates the conditions for the assessment of the effectiveness of learning. There are different methods of development of cooperation skills: "Team academic performance of students", "Mosaic", "Tour in art gallery", "Free composition in five minutes", etc. The use of the indicated methods supposes the encouragement of thoughts and ideas, the absence of any criticism, the equality of students, taking part in the lesson, record of thoughts and aimed at the solution of any educational task. It is advisable to apply these methods at different stages of the lesson in any subject in order to solve a specific educational problem and develop students’ creative thinking, imagination, self-confidence, and the formation of cooperation skills. As a result of the study, we came to a conclusion that the technology of learning in cooperation and methods containing the elements of learning in cooperation contribute to the creation of opportunities for the achievement of success for each student, as well as stimulating and welcoming atmosphere in the classroom. The effectiveness of learning in cooperation is conditioned by the small size of the group of participants, the analysis of the proposed solutions and tasks and their practical application in the future. Key words: learning process, learning technology, learning method, learning in cooperation, technology of learning in cooperation, cooperation skills, record of thoughts, creative thinking, "Team academic performance of students", "Mosaic", "Tour in art gallery", "Free composition in five minutes", etc.